"Bursts of a campaign" (1962). A recovered text by Jos´e-Miguel Ullán - Blesa, Túa; Titos, Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
During summer 1962, a 17-years old José-Miguel Ullán took part in a Literacy Campaign organized by the University Service of Labour (Servicio Universitario del Trabajo, SUT), integrated in the Spanish University Union (Sindicato Español Universitario, SEU). He worked and lived together with the people of El Almendral, a very small village next to the town of Zafarraya, in the province of Granada. Shortly after his arrival, he began to write a series of short articles, or “bursts”, sharing his impressions and experiences were published in the local newspapers Ideal during July and August 1962. These juvenile texts, the first ones known to have been signed by the author, remained lost inside the pages of a provincial daily and had never been cited when studying the works and evolution of Ullán, who then became a renowned poet from Salamanca. This paper focuses on its recovery and analysis.
Keywords: José-Miguel Ullán; SUT; SEU; literacy